2002
DOI: 10.1016/s0886-3350(01)01079-3
|View full text |Cite
|
Sign up to set email alerts
|

Retained intravitreal lens fragments after phacoemulsification: Complications and visual outcome in vitrectomized and nonvitrectomized eyes

Abstract: Intraocular inflammation, increased IOP, and CME were major complications in nonvitrectomized eyes after phacoemulsification; retinal detachment occurred in 2 vitrectomized eyes. In eyes with intravitreal lens fragments after phacoemulsification, vitrectomy can yield faster visual rehabilitation and better quality of vision. Conservative management is feasible at the price of long-term intraocular inflammation and slower restoration of comparable visual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 9 publications
2
31
0
2
Order By: Relevance
“…This percentage is apparently lower compared with other published series with 41-82% of cases achieving a final visual acuity of 6/12 or better, regardless of the time interval between cataract and vitreous surgery. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]24 This may be due to a large proportion (31%) of our cases having pre-existing ocular diseases before cataract surgery, with an overall median preoperative visual acuity of 6/90. In the series by Kageyama et al, 5 the median preoperative visual acuity was 6/15 with only 12% of cases had pre-existing ocular comorbidity.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This percentage is apparently lower compared with other published series with 41-82% of cases achieving a final visual acuity of 6/12 or better, regardless of the time interval between cataract and vitreous surgery. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]24 This may be due to a large proportion (31%) of our cases having pre-existing ocular diseases before cataract surgery, with an overall median preoperative visual acuity of 6/90. In the series by Kageyama et al, 5 the median preoperative visual acuity was 6/15 with only 12% of cases had pre-existing ocular comorbidity.…”
Section: Discussionmentioning
confidence: 92%
“…This is an important finding since secondary glaucoma had been reported in 5-41% in previous studies in which pars plana vitrectomy was performed later. 6,8,10,[13][14][15]20,21,24 Blodi et al 9 also showed that early pars plana vitrectomy within 3 weeks decreased the rate of chronic glaucoma. Wilkinson and Green 22 have shown that in 135 consecutive vitreous specimens that were obtained during vitreous surgery for retained lens material after surgery for senile cataract, no inflammatory cells were found in which vitrectomy was performed within 3 days of cataract surgery while lensinduced inflammatory reaction increased as the time interval of surgeries increased.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations